Perbandingan Terapi Laser Tingkat Rendah Dan Terapi Laser Intensitas Tinggi Terhadap Nyeri Dan Kemampuan Fungsional Pada Osteoarthritis Lutut - Setia Wati Astri; Nyoman Murdhana; Nury Nusdwinuringtyas; Aria Kekalih; Peggy Sunarjo; Ferius Soewito (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Osteoarthritis (OA) of the knee causes disability due to pain and will affect the functional ability to walk. Low-Level Laser Therapy (LLLT) has been shown to reduce pain in knee OA, while High Intensity Laser Therapy (HILT) is able to reach deeper joint areas. Method: This study aimed to compare the effect differences between LLLT and HILT on pain and functional capacity in knee OA. Methods: This is a double-blind randomized controlled trial with 61 subjects randomized into LLLT (n=31) and HILT (n=30) groups. All the subjects were knee OA patient with Visual Analog Scale (VAS) ≥ 4. The laser therapy and exercise were given 3 times per week for 6 sessions. The pain scale evaluated using VAS and functional ability evaluated using 50-feet walk test. Result: After 6 sessions, both LLLT and HILT group showed reduced VAS score [∆VAS Score LLLT = 3 (2 – 4), HILT = 3 (2 – 5)] and increased walking speed (∆ walking speed for LLLT = 0.23 (0.02 – 1.24) m/s, HILT = 0.22 (0.08 – 0.7) m/s) which were statistically (p less than 0.001) and clinically significant. HILT group had faster walking speed and greater VAS reduction compared to LLLT group (p less than 0.001), but there was no significant difference in walking speed between two groups (p=0.655). Conclusion: HILT and LLLT combined with exercise were effective in reducing pain and increasing functional ability in knee OA after 6 sessions of intervention. Pain and functional ability improvement was faster and greater in HILT group than LLLT group.